The individual face to face with public health: a conflict of interests or a conflict of conditions? - Janusz Sytnik-Czetwertyński; Dorota Cianciara (Kazimierz Wielki University, 2016)
Sytnik-Czetwertyński Janusz, Cianciara Dorota. The individual face to face with public health: a conflict of interests or a conflict of conditions? Journal of Education, Health and Sport. 2016;6(2):223-237. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46590 http://ojs.ukw.edu.pl/index.php/johs/article/view/3394 https://pbn.nauka.gov.pl/works/716770     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016.     The individual face to face with public health: a conflict of interests or a conflict of conditions?   Janusz Sytnik-Czetwertyński   Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Poland   Dorota Cianciara   Institute of Epidemiology and Health Promotion, School of Public Health Medical Centre for Postgraduate Education, Warsaw, Poland     Abstract The freedom of man and the freedom of the citizen are two entirely different domains. By nature, man is created for freedom, yet he does not possess the ability to effectively provide himself with a feeling of security. Man is therefore forced to negotiate, and in exchange for the abandonment of certain rights to freedom, receives a guarantee of relative peace. In order to enforce its obligations, the state is sometimes forced, in the name of the public good, to pacify the intentions of the individual and enforce pro-social actions. The issue discussed here is therefore reduced to the following: is the domain of public health one of those which should remain under the complete, or merely partial, control of the state (such as defence for instance), or should it remain open to the rights and demands of citizens?   The conclusion seems to be the following: the public health perspective is a social one and there is therefore little room for a wide-ranging dialogue with the individual. On the other hand, the system cannot close itself entirely to the reactions of society, since it is supposed to serve people and not its own ideals. It must possess the capacity to not lose sight of people and their problems, so often defying any prognoses and expectations, within the process of enacting public health policy.     Key words: face to face, public health.